Microstructure and Abrasive Wear Resistance of Mo2C Doped Binderless Cemented Carbide - Zan, Xiuqi; Shi, Kaihua; Dong, Kailin; Shu, Jun; Liao, Jun (Frontiers in Materials, 2020)
A series of binderless cemented carbides with various Mo2C addition amounts(0~6wt.%) were prepared by sintering and then HIPed at 2000℃ under an isostatic pressure of 70MPa. The microstructure and abrasive wear resistance of the obtained samples were systemically investigated. The grain size does not change with the increase of Mo2C addition amount, while the abrasive wear resistance of the cemented carbide increases obviously. The data of the abrasive wear test show the wear volume loss of the cemented carbide reduces from 7.32cm3/105r to 0.02cm3/105r when the Mo2C addition amount change from 0wt.% to 6.0wt.%. The superior abrasion resistance of samples with higher Mo2C content and the smoother appearance of the worn surfaces with no pronounced pullout of grains compared with other samples were result from the forming of (W,Mo)C because of the intermixing between WC and Mo2C after sintering at a high temperature.